ANALISIS STRUKTUR ASPEK TOKOH DAN PENOKOHAN PADA NOVEL LA BARKA DALAM PERSPEKTIF ISLAM - Leli Nisfi Setiana (TRANSFORMATIKA, 2017)
The position of men and women in religion is equal. In short, Islam has said that the position of men and women is equal. Women may have an activity or work in certain field at home or in the government or private institution as long as those activities are keep their dignity, religion and politeness. Moreover, the working women who have an activity outside should be in a safe condition to avoid the negative effects. A number of negative effect happened on working women make the distinction between psychological activity and the characterization in La Barka novel in Islamic perspective. Therefore, this research will analyze the psychological of character and characterization in La Barka novel through Islamic perspective. Keywords: Structure analysis, Character and characterization aspects, LA BARKA Novel, Islamic perspective